2017
DOI: 10.5455/njppp.2018.8.1144629112017
|View full text |Cite
|
Sign up to set email alerts
|

Influence of altered circadian rhythm on quality of sleep and its association with cognition in shift nurses

Abstract: Background: Exposure to shift works and especially to night shifts goes against the circadian rhythm of the social man which brings about a multitude of disruptive effects on health such as sleep disturbances, day sleepiness, decreased cognitive performance, fatigue, increased risk of accidents, poor quality of life, and vigilance troubles. Aims and Objectives: Evaluate sleep quality and its association with cognition among hospital shift working nurses. Materials and Methods: This is a cross-sectional study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Researchers have found that nurses on shift work frequently report sleep problems, including poorer sleep quality, sleep disturbances, sleep deprivation, and excessive sleepiness [8][9][10][11]. Poor sleep quality is prevalent among nurses worldwide [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that nurses on shift work frequently report sleep problems, including poorer sleep quality, sleep disturbances, sleep deprivation, and excessive sleepiness [8][9][10][11]. Poor sleep quality is prevalent among nurses worldwide [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained align with previous research in the health and psychological field (Hendriksen et Even though subjective vitality can be linked to specific physical signals of individuals, particularly night workers, its effect was observed more firmly on the perception of the status of mental health. The scope of the literature derived from night work studies is based on the circadian chronobiological cycle disorder, which plays a fundamental role in the modulation of human emotions and, therefore, can cause alterations in some functions of the behavior of individuals (Vijaykumar et al, 2018). Not surprisingly, relationships have been established between the molecular mechanisms of circadian rhythms and psychiatric pathologies, such as anxiety, bipolar disorder, depression, hyperactivity, and even schizophrenia (Vogel et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Many individuals in various trades and professions require the ability to actively perform their duties (remain alert) during unconventional working hours, such as night shifts. However, such activities can burden one's mental and physical health due to the frequent interruptions in circadian rhythm, which is motivated by an irregular sleep pattern (Vijaykumar et al, 2018). Specifically, jobs oriented to the security functions are intended to protect and ensure the integrity and wellbeing of people and assets.…”
Section: Introductionmentioning
confidence: 99%
“…The MEQ has 19 items, and its total score ranges from 16 to 86, with higher scores indicating more morningness and lower scores indicating more eveningness. There are 5 classifications based on the MEQ score: Definitely morning type (score 70-86), moderately morning type (score 59-69), neither type (score 42-58), moderately evening type (score 31-41), and definitely evening type (score [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Its internal consistency using Cronbach's alpha coefficient is 0.86, with favorable test-retest reliability.…”
Section: Methodsmentioning
confidence: 99%